Effectiveness Of Finger Appliance Combined With A Z-Spring In The Management Of Maxillary Multiple Diastema And Midline Shift: A Case Report - Annisa Rachmah Afrizal; Bramita Beta Arnanda (International Journal of Health Engineering and Technology, 2026)
Malocclusion can affect both oral aesthetics and function, one manifestation of which is multiple diastema, defined as spaces between two or more adjacent teeth. This condition is often accompanied by a maxillary midline deviation, which may compromise dental aesthetics and occlusal harmony. The management of multiple diastema requires a multidisciplinary approach aimed at closing interdental spaces, correcting midline deviation, and eliminating etiological factors. Removable orthodontic appliances may serve as a viable treatment option because they are simple, easy to fabricate, and more cost-effective than fixed appliances. This case report aims to describe the management of maxillary multiple diastema associated with midline deviation using a removable orthodontic appliance in the form of an active plate. A 24-year-old female patient presented with spacing between the anterior teeth of the maxillary arch. Clinical examination and supporting analyses revealed a skeletal Class III relationship with a maxillary arch excess space of 1.6 mm. The treatment plan focused on the closure of multiple diastema and correction of the maxillary midline deviation using an active plate. Periodic activation of the appliance was performed to achieve tooth movement for space closure and midline correction. Evaluation after three months of treatment demonstrated successful closure of the multiple diastema and improvement of the maxillary midline while maintaining normal occlusal relationships. This case report concludes that removable orthodontic treatment using an active plate is effective for diastema closure and midline correction in selected mild-to-moderate cases, particularly in cooperative adult patients.